Analysis Of The Tempe Supply Chain In Lambusa Village, Konda District, Konawe Selatan Regency (Case Study Of Novia Ayu's Industry) - Insyira Afifah Bakri; Abdul Gafaruddin; Munirwan Zani (Cita konsultindo, 2023)
This study aims to find out how product flow, financial flow and information flow in the tempe Novia Ayu supply chain in Lambusa Village, Konda District, Konawe Selatan Regency. This study was analyzed using descriptive analysis methods and calculating marketing margins in this case costs and profits. The results showed that supply chain flows consisting of product flows, information flows, and financial flows in both supply chains were in accordance with the requests and agreements of supply chain actors, including the timeliness and arrival of tempe products. There are two marketing channels in this study, namely, marketing channel I: production input → tempe Novia Ayu → final consumer, marketing channel II: production input → tempe Novia Ayu → retailer → end consumer. Based on the tempe marketing channel in Lambusa Village, Konda District, South Konawe Regency, it shows that the level of marketing efficiency varies in each marketing agency. In addition, the marketing channel that has the most efficient value is located on marketing channel I.